2018
DOI: 10.3390/w10050539
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprints of Vegetable Crop Wastage along the Supply Chain in Gauteng, South Africa

Abstract: Food production in water-scarce countries like South Africa will become more challenging in the future because of the growing population and intensifying water shortages. Reducing food wastage is one way of addressing this challenge. The wastage of carrots, cabbage, beetroot, broccoli and lettuce, produced on the Steenkoppies Aquifer in Gauteng, South Africa, was estimated for each step along the supply chain from the farm to the consumer. Water footprints for these vegetables were used to determine the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Three papers in this volume approach the water footprint from a supply-chain rather than from a geographic perspective. One paper considers water consumption along the supply chain of wheat bread [21], while another paper considers the water footprint of food waste along the chain [22]. A third paper studies the relation between the demand for biofuels and green water resources use and scarcity [23].…”
Section: Water Footprint Reduction Through Supply-chain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Three papers in this volume approach the water footprint from a supply-chain rather than from a geographic perspective. One paper considers water consumption along the supply chain of wheat bread [21], while another paper considers the water footprint of food waste along the chain [22]. A third paper studies the relation between the demand for biofuels and green water resources use and scarcity [23].…”
Section: Water Footprint Reduction Through Supply-chain Managementmentioning
confidence: 99%
“…Roux et al [22] assess the blue water footprint of vegetable crop wastage along the supply chain in a case for South Africa. They focus on food waste in the value chain rather than the food finally consumed at the end of the value chain.…”
Section: Water Footprint Reduction Through Supply-chain Managementmentioning
confidence: 99%
“…The results found that 70% of the food wastage occurred on-farm at the packhouse. The results was obtained "from a large commercial farm that uses advanced technologies" (Le Roux et al, 2017). The average calculated wastage of the mentioned five vegetables along the supply chain is lower than previous estimates by Oelofse and Nahman (2013).…”
mentioning
confidence: 91%
“…Lettuce has higher average wastage percentages (38%) as compared to cabbage (14%) and broccoli (13%). The wastage varies depending on the season and it is noted that some of the waste is used for beneficial purposes including animal feed and composting (Le Roux et al, 2017). A summary of their findings by commodity group along the supply chain by is provided in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation